Fashion Fluidity: A Study on Gen Z’s Awareness, Acceptance, and Sustainable Purchase Intentions of Androgynous Clothing - John, Dr. Jiju Mathew; Jain, Dr. Rajeshwari; Patel, Dr. Neha (International Journal of Aquatic Research and Environmental Studies, 2025)
Despite its creativity, the fashion industry remains one of the most environmentally unsustainable sectors. Genderless (androgynous) fashion has emerged as a potential solution, reducing overproduction, extending garment life, and challenging gender norms. This study investigates how Generation Z in Ahmedabad, India, perceives and adopts genderless fashion, focusing on awareness, acceptance, and purchase intention. Data from 542 respondents were analysed using PLS-SEM. Findings reveal limited awareness (45.4%) and early-stage adoption, though many believe it promotes inclusivity and sustainability. Social acceptance remains a significant barrier, creating discomfort in the public adoption process. Purchase intentions are influenced by peers, sustainability awareness, and branding, yet moderated by affordability and cultural norms. The findings reveal that while awareness remains limited and adoption is still in its early stages, Gen Z demonstrates a dual orientation—simultaneously resisting and embracing genderless fashion depending on contextual and psychological factors. Importantly, the study highlights that social acceptance and cultural comfort act as significant barriers, while peer influence, sustainability consciousness, and brand communication have a positive influence on adoption intention.